Powder for electrode, method for manufacturing powder, electrode for secondary battery including powder, and method for manufacturing electrode
By controlling the degree of fibrosis in the electrode powder, the problem of difficulty in quantifying the degree of fibrosis of the dry electrode is solved, and electrode preparation with high energy density and processability is achieved, ensuring the physical and electrochemical characteristics of the electrode.
Patent Information
- Application Number
- CN202311730325.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-06-16
- Filing Date
- 2023-12-15
- Publication Date
- 2024-12-17
AI Technical Summary
The prior art is difficult to quantify and standardize the degree of fibrosis of dry electrodes, affecting the physical and electrochemical characteristics of the electrodes, and the amount of analysis through image analysis is limited, making it difficult to be repeatable and representative.
A powder for electrodes, including active substances, solid electrolytes, conductive materials and fibrous binders, is provided, and the fibrous degree is controlled within the range of 2.7≤E11/E8≤3.6 through specific stirring conditions and crushing processes, and is also used to control the fibrosis degree. High energy density electrodes are prepared by dry mixing and kneading processes.
The degree of fibrosis of the dry electrode is quantified and standardized, the ionic conductivity, specific capacity and energy density of the electrode are improved, and the high energy density and processability of the electrode are ensured.
Smart Images

Figure CN119153694A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a powder for an electrode, a method for producing the powder, an electrode for a secondary battery comprising the powder, and a method for producing the electrode. Background Art
[0002] Recently, in order to develop high energy density battery specifications and improve processability, a method of manufacturing an electrode by a dry process without using a solvent, and a fiberized binder is used in the dry process, has attracted attention.
[0003] Since the degree of fiberization of the electrode affects not only the physical properties of the electrode but also the electrochemical properties of the electrode, the degree of fiberization of the electrode is an important factor in designing a dry electrode. Depending on the degree of fiberization of the binder, physical properties such as the tensile strength and density of the electrode are affected, and since the electron / ion conductivity path is blocked, the electrochemical properties are also controlled.
[0004] Typically, the degree of fibrosis is confirmed by measuring the thickness and length of the fibers through image analysis, but since the amount of analysis by image analysis alone is limited, it is difficult to be reproducible and representative. Therefore, it is necessary to quantify and standardize the degree of fibrosis of dry electrodes. Summary of the invention
[0005] The present invention is directed to solving the above-mentioned problems associated with the prior art.
[0006] The degree of fiberization of electrode powders used for dry electrodes can be quantified and standardized.
[0007] In one embodiment, the present invention provides a powder for an electrode, which meets the fiberization degree proposed in the present invention and can be suitable for the design of a high energy density electrode.
[0008] The objects of the present invention are not limited to the above objects. The objects of the present invention will become more apparent from the following description and will be achieved by the means described in the appended claims and their combinations.
[0009] In an exemplary embodiment, the present invention provides a powder for an electrode, the powder including an active material, a solid electrolyte, a conductive material, and a fibrous binder, and satisfying the following Conditional Expression 1.
[0010] [Conditional expression 1]
[0011] 2.7≤Fibrosis degree (E 11 / E 8 )≤3.6
[0012] [Formula 1]
[0013]
[0014] In conditional expression 1, E 11 represents the E of the eleventh cycle calculated by formula 1 cycle value.
[0015] In conditional expression 1, E 8 represents the E of the eighth cycle calculated by formula 1 cycle value.
[0016] In Formula 1, T, F, and H represent the torque applied to the blade, the force applied to the blade, and the measured depth, respectively. For each cycle from the first cycle to the eighth cycle, the blade can stir the powder in the container at 100 rpm while descending and then ascending the measured depth. For the ninth cycle to the eleventh cycle, while descending and then ascending the measured depth, the blade can stir the powder in the container at a rotation speed lower than 100 rpm, and the rotation speed of the eleventh cycle is 10 rpm. While descending and then ascending the measured depth, the blade can stir the powder in the container at a rotation speed of 70 rpm in the ninth cycle and at a rotation speed of 40 rpm in the tenth cycle.
[0017] The fibrous binder may include polytetrafluoroethylene (PTFE). The active material may include NCM811, the solid electrolyte may include LPSCl, and the conductive material may include VGCF.
[0018] The length of the fibrous binder may be in the range of 4 mm to 5 mm.
[0019] The diameter of the fibrous binder may be in the range of 0.01 μm to 20 μm.
[0020] The fibrous binder is used in an amount ranging from 0.5 wt % to 10 wt % based on 100 wt % of the powder for an electrode.
[0021] An electrode for a secondary battery according to the present invention may include the powder for an electrode according to the present invention.
[0022] The electrode may be an electrode for a lithium-ion battery or an electrode for an all-solid lithium battery.
[0023] The electrode may satisfy at least one of an ionic conductivity ranging from 0.20 mS to 0.50 mS, a specific capacity ranging from 190 Ah / g to 193 Ah / g, a composite density ranging from 3.40 g / cc to 3.55 g / cc, and an energy density ranging from 550 mAh to 580 mAh.
[0024] The method of manufacturing a powder for an electrode according to the present invention may include: manufacturing a mixture by dry mixing an active material, a solid electrolyte, a conductive material, and a particulate binder; mixing the mixture to manufacture a mixture mass; and pulverizing the mixture mass to manufacture the powder for an electrode.
[0025] The mixing operation may include a kneading process using a kneader.
[0026] The kneading process may be performed at a temperature ranging from 50° C. to 120° C. for 5 minutes to 30 minutes.
[0027] The pulverization operation can be performed using a screen having a particle size ranging from 400 μm to 600 μm.
[0028] The method of manufacturing an electrode for a secondary battery according to the present invention may include: depositing the powder for an electrode according to the present invention to manufacture a composite film; and forming and laminating the composite film on at least one surface of a current collector to manufacture a dry electrode.
[0029] A secondary battery according to the present invention may include a positive electrode manufactured based on the method of manufacturing an electrode for a secondary battery according to the present invention, a negative electrode, and an electrolyte interposed between the positive electrode and the negative electrode.
[0030] As discussed, the method and system suitably include the use of a controller or processor.
[0031] In another embodiment, a vehicle comprising a device as disclosed herein is provided.
[0032] Other embodiments and preferred embodiments of the invention are discussed below.
[0033] The above features and other features of the present invention are discussed below. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] The above and other features of the present invention will now be described in detail with reference to certain exemplary embodiments of the invention shown in the accompanying drawings, which are given hereinafter by way of illustration only and therefore do not limit the present invention, and in which:
[0035] Figure 1 An apparatus for measuring the degree of fibrosis according to the present invention is shown;
[0036] Figure 2 The blade portion of the instrument for measuring the degree of fibrosis according to the present invention is shown;
[0037] Figure 3 A method for manufacturing an electrode for a secondary battery according to the present invention is shown;
[0038] Figure 4 A scanning electron microscope (SEM) photograph of the fibrous binder of Comparative Example 1 is shown;
[0039] Figure 5 A scanning electron microscope (SEM) photograph of the fibrous binder of Example 1 is shown.
[0040] Figure 6 A scanning electron microscope (SEM) photograph of the fibrous binder of Example 2 is shown.
[0041] Figure 7 A scanning electron microscope (SEM) photograph of the fibrous binder of Comparative Example 2 is shown.
[0042] It should be understood that the accompanying drawings are not necessarily drawn to scale, but rather represent somewhat simplified representations of various features illustrating the basic principles of the invention. The specific design features of the present invention as described herein, including such as specific dimensions, orientations, locations, and shapes will be determined in part by the specific intended application and use environment.
[0043] In the drawings, like reference numerals refer to the same or equivalent parts of the present invention throughout the several figures of the drawing. DETAILED DESCRIPTION
[0044] The above and other purposes, features and advantages of the present invention will become more apparent through the following description of exemplary embodiments with reference to the accompanying drawings. However, the present invention is not limited to the embodiments disclosed herein and may be implemented in other forms. On the contrary, the embodiments disclosed herein are provided so that the present invention is complete and complete, and the spirit of the present invention is fully conveyed to those skilled in the art.
[0045] When describing each of the accompanying drawings, similar reference numerals are assigned to similar components. In order to make the present invention clear, in the accompanying drawings, the size of the structure is shown in an enlarged scale. Although the terms "first", "second", etc. can be used to describe various components, these components should not be limited by these terms. These terms are only used to distinguish one component from another component. For example, without departing from the scope of the present invention, a first component may be referred to as a second component, and similarly, a second component may also be referred to as a first component. Unless the context clearly indicates otherwise, the singular form also includes the plural form.
[0046] It should be understood that the terms "include", "comprising", "having" specifically specify the presence of the features, values (number), steps, operations, components, elements or their combinations described herein, but do not exclude the presence or addition of one or more other features, values, steps, operations, components, elements or their combinations. In addition, when a portion of a layer, film, region or plate, etc. is referred to as being "on" another portion, this includes not only the case where the portion is directly on the other portion, but also the case where there is another portion (another portion) between the portion and the other portion. Similarly, when a portion of a layer, film, region or plate is referred to as being "under" another portion, this includes not only the case where the portion of the layer, film, region or plate is directly under the other portion, but also the case where there is another portion between the portion and the other portion.
[0047] It should be understood that the term "vehicle" or "vehicular" or other similar terms used herein include motor vehicles, generally such as passenger cars including sport utility vehicles (SUVs), buses, trucks, various commercial vehicles, watercraft including various boats and ships, aircraft, etc., and include hybrid vehicles, electric vehicles, plug-in hybrid vehicles, hydrogen-powered vehicles and other alternative fuel vehicles (e.g., fuels from resources other than petroleum). As referred to herein, a hybrid vehicle is a vehicle having two or more power sources, such as a gasoline-powered vehicle and an electric vehicle.
[0048] The terms used in this article are only used to describe specific embodiments and are not intended to limit the present invention. As used herein, unless the context clearly states otherwise, the singular forms "one", "an" and "the" are intended to also include plural forms. These terms are only intended to distinguish one component from another component, and these terms do not limit the nature, sequence or order of the components constituted. It will be further understood that when used in this specification, the terms "include" and / or "comprising" specify the existence of stated features, integers, steps, operations, elements and / or components, but do not exclude the existence or addition of one or more other features, integers, steps, operations, elements, components and / or their groups. The term "and / or" used in this article includes any one of one or more of the listed related terms and all combinations. Throughout the specification, unless clearly described to the contrary, the word "include" and such as "comprising" or "containing" deformation will be understood to imply the inclusion of stated elements but do not exclude any other elements. In addition, the terms "unit", "-device", "-means" and "module" described in this specification mean a unit for processing at least one function or operation, and can be implemented by hardware components or software components and their combination.
[0049] Although the exemplary embodiment is described as using multiple units to perform the exemplary process, it should be understood that the exemplary process can be performed by one or more modules. In addition, it should be understood that the term controller / control unit refers to a hardware device that includes a memory and a processor and is specifically programmed to perform the process described herein. The memory is configured to store the module and the processor is specifically configured to run the module to perform one or more processes described further below.
[0050] Further, the control logic of the present invention may be implemented as non-transitory computer readable media on a computer readable medium containing executable program instructions executed by a processor, controller, etc. Examples of computer readable media include, but are not limited to, ROM, RAM, compact disk (CD)-ROMs, magnetic tapes, floppy disks, flash drives, smart cards, and optical data storage devices. The computer readable medium may also be distributed in network-connected computer systems so that the computer readable medium is stored and executed in a distributed manner, for example, by a telematics server or a controller area network (CAN).
[0051] Unless otherwise specified or apparent from the context, the term "about" as used herein should be understood to be within the normal tolerance range in the art, such as within 2 standard deviations of the mean. "About" can be understood to be within 10%, 9%, 8%, 7%, 6%, 5%, 4%, 3%, 2%, 1%, 0.5%, 0.1%, 0.05% or 0.01% of the specified value. Unless otherwise apparent from the context, all numerical values provided herein are modified by the term "about".
[0052] In addition, when numerical ranges are disclosed herein, such numerical ranges are continuous, and unless otherwise indicated, numerical ranges include all values from the minimum value to the maximum value. Further, when numerical ranges refer to integers, unless otherwise indicated, the numerical ranges include all integers from the minimum value to the maximum value.
[0053] The powder for the electrode may include an active material, a solid electrolyte, a conductive material, and a fibrous binder.
[0054] The electrode may be a positive electrode, and the active material may be a positive electrode active material.
[0055] There is no limitation on the positive electrode active material as long as it is in the form of lithium transition metal oxide, lithium metal iron phosphorus oxide or metal oxide, and may include, for example, layered compounds such as lithium cobalt oxide (LiCoO 2 ) and lithium nickel oxide (LiNiO 2 ), or compounds substituted with one or more transition metals; lithium manganese oxides, such as LiMnO 3 、LiMn 2 O 3 and LiMnO 2 , by the chemical formula Li 1+x Mn 2-x O 4 represents (where x ranges from 0 to 0.33); lithium copper oxide (Li 2 CuO 2 ); Vanadium oxides such as LiV 3 O 8 、LiFe 3 O 4 、V 2 O 5 and Cu 2 V 2 O 7 ; Ni site type lithium nickel oxide, composed of the chemical formula LiNi 1-x M x O 2represented by (where M = Co, Mn, Al, Cu, Fe, Mg, B or Ga, and x = 0.01 to 0.3); lithium manganese composite oxide, with the chemical formula LiMn 2-x M x O 2 (where M = Co, Ni, Fe, Cr, Zn or Ta, and x = 0.01 to 0.1) or Li 2 Mn 3 MO 8 (where M = Fe, Co, Ni, Cu or Zn); LiMn 2 O 4 , where the Li part of the chemical formula is replaced by alkaline earth metal ions; lithium metal phosphide oxide LiMPO 4 (where M = Fe, CO, Ni or Mn); disulfide compound; and Fe 2 (MoO 4 ) 3 , but the present invention is not limited thereto.
[0056] The electrode can be a negative electrode, and the active material can be a negative electrode active material.
[0057] The following substances can be used as the negative electrode active material: carbon, such as non-graphitized carbon or graphitized carbon; metal composite oxides, such as Li x Fe 2 O 3 (0 ≤ x ≤ 1), Li x WO 2 (0 ≤ x ≤ 1) or Sn x Me 1-x Me' y O z (Me is Mn, Fe, Pb or Ge, Me' is Al, B, P or Si, group 1, 2, 3 elements of the periodic table, halogens, 0 < x ≤ 1, 1 ≤ y ≤ 3, and 1 ≤ z ≤ 8); lithium metal; lithium alloy; silicon-based alloy; tin-based alloy; silicon-based oxides, such as SiO, SiO / C and SiO 2 ; metal oxides, such as SnO, SnO 2 , PbO, PbO 2 , Pb 2 O 3 , Pb 3 O 4 , Sb 2 O 3 , Sb 2 O 4 , Sb 2 O 5 , GeO, GeO 2 , Bi2 O 3 、Bi 2 O 4 and Bi 2 O 5 ; conductive polymers such as polyacetylene; or Li-Co-Ni based substances.
[0058] The electrode may be preferably a positive electrode, and the active material may be a positive electrode active material, and more specifically, may be a lithium nickel manganese cobalt-based oxide (LiNi 0.8 Co 0.1 Mn 0.1 O 2 ; NCM811).
[0059] As a component responsible for lithium ion conduction of an electrode including a solid electrolyte, the solid electrolyte may be a sulfide-based solid electrolyte or an oxide-based solid electrolyte.
[0060] The solid electrolyte may be a solid electrolyte according to the following Chemical Formula 1.
[0061] [Chemical formula 1]
[0062] L a M b P c S d X e
[0063] (In Chemical Formula 1, L is one or more elements selected from the group consisting of alkali metals, M is one or more elements selected from the group consisting of B, Aλ, Ga, In, Si, Ge, Sn, Pb, As, Sb, Bi, Ti, V, Mn, Fe, Co, Ni, Cu, Y, Zr, Nb, Mo, Tc, Ru, Rh, Pd, Ag, Hf, Ta and W, X is an element selected from the group consisting of F, Cl, Br, I and O, 0≤a≤12, 0≤b≤6, 0≤c≤6, 0≤d≤12, 0≤e≤9).
[0064] For example, the solid electrolyte may include one or more selected from the group consisting of: Li 6 PS 5 Cl, Li 2 SP 2 S 5 , Li 2 SP 2 S 5 -LiI, Li 2 SP 2 S 5 -LiCl, Li 2 SP 2 S5 -LiBr, Li 2 SP 2 S 5 -Li 2 O. Li 2 SP 2 S 5 -Li 2 O-LiI、Li 2 S-SiS 2 , Li 2 S-SiS 2 -LiI, Li 2 S-SiS 2 -LiBr, Li 2 S-Si 2 -LiCl, Li 2 S-SiS 2 -B 2 S 3 -LiI, Li 2 S-SiS 2 -P 2 S 5 -LiI, Li 2 SB 2 S 3 , Li 2 SP 2 S 5 -Z m S n (m and n are positive numbers, Z is one of Ge, Zn and Ga), Li 2 S-GeS 2 , Li 2 S-SiS 2 -Li 3 PO 4 , Li 2 S-Si 2 -Li x MO y (x and y are positive numbers, M is one of P, Si, Ge, B, Al, Ga and In), and LiGeP 2 S 12 .
[0065] There is no particular limitation on the conductive material, as long as the material has conductivity without causing chemical changes in the battery. For example, the conductive material may include: graphite, including natural graphite and artificial graphite; carbon-based materials, including carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, and summer black; conductive fibers, including carbon fibers and metal fibers; metal powders, including carbon fluoride powders, aluminum powders, and nickel powders; conductive whiskers, including zinc oxide and potassium titanate; conductive metal oxides, including titanium oxide; and conductive materials including polyphenylene derivatives. Specifically, in order to uniformly mix the conductive material and improve the conductivity, one or more selected from the group consisting of activated carbon, graphite, carbon black, and carbon nanotubes may be included, and more specifically, activated carbon may be added.
[0066] The conductive material may preferably be vapor grown carbon fiber (VGCF).
[0067] The fibrous binder may include PTFE.
[0068] The length of the fibrous binder may be in the range of about 4 mm to about 5 mm.
[0069] The diameter of the fibrous binder may be in the range of about 0.01 μm to about 20 μm.
[0070] The fibrous binder may be used in an amount ranging from about 0.5 wt % to about 10 wt % based on 100 wt % of the powder for an electrode.
[0071] When the content of the binder exceeds the above range and is too small, the formability is poor, so there is a disadvantage of difficulty in manufacturing a uniform clay type electrode. When the content of the binder is too high, the denier cannot be controlled and the binder will agglomerate, so there is a disadvantage of increased electrode resistance.
[0072] Recently, in order to develop high energy density battery specifications and improve processability, a method of manufacturing electrodes by a dry process without using a solvent, and a fiberized binder is used in the dry process, has attracted attention.
[0073] The degree of fiberization of the electrode is an important factor in designing dry electrodes because it affects not only the physical properties of the electrode but also the electrochemical properties of the electrode. Depending on the degree of fiberization of the binder, physical properties such as the tensile strength and density of the electrode are affected, and the electrochemical properties are also controlled because the electron / ion conductive paths are blocked.
[0074] Typically, the degree of fibrosis is confirmed by measuring the thickness and length of the fibers through image analysis, but due to the limited amount of analysis through image analysis alone, it is difficult to be reproducible and representative. Therefore, it is necessary to quantify and standardize the degree of fibrosis of dry electrodes.
[0075] The present invention relates to an electrode including fibrous PTFE as a binder. PTFE is a polymer in which all hydrogens of PE are replaced by fluorine. Although PTFE is a polymer with an aliphatic main chain, PTFE has excellent thermal stability and electrical stability and is widely used in the field of electronic materials. In particular, the highest occupied molecular orbital (HOMO) level of the polymer is low and the oxidation stability is high, so PTFE is applied to the positive dry electrode. The glass transition temperature (T g ) is about 120°C, but because the β transition temperature is lower than room temperature, PTFE has fibrosis characteristics when pressure is applied.
[0076] PTFE can control the thickness and length of the fiber through the kneading process, and the more fiberization occurs, the better the bonding ability of the electrode powder, so that less electrode desorption can occur during charge / discharge. However, since the electron / ion conductive path will be blocked, the electrochemical characteristics will change, and the composite density will be reduced, it is very important to control the fiberization degree of PTFE in the electrode.
[0077] Typically, the degree of fibrosis is confirmed by measuring the thickness and length of the fibers through image analysis, but due to the limited amount of analysis through image analysis alone, it is difficult to be reproducible and representative. Therefore, it is necessary to quantify and standardize the degree of fibrosis of dry electrodes.
[0078] Therefore, the present invention proposes a method of standardizing the degree of fiberization and indicates that a powder for an electrode having a degree of fiberization between about 2.7 and about 3.6 can be implemented as a high energy density electrode.
[0079] Figure 1 An apparatus for measuring the degree of fibrosis according to the present invention is shown. Figure 1 , the powder can satisfy the following conditional expression 1.
[0080] [Conditional expression 1]
[0081] 2.7≤Fibrosis degree (E 11 / E 8 )≤3.6
[0082] [Formula 1]
[0083]
[0084] In conditional expression 1, E 11 represents the E of the eleventh cycle calculated by formula 1 cycle value.
[0085] In conditional expression 1, E 8 represents the E of the eighth cycle calculated by formula 1 cycle value.
[0086] In Formula 1, T, F, and H represent torque, force, and measurement depth, respectively.
[0087] T, F, and H in Formula 1 are obtained by a measuring instrument including: a cylindrical body portion; and a blade portion installed on the body portion to rotate and configured to ascend and descend.
[0088] Figure 2 FIG. 2 shows a blade portion of an instrument for measuring the degree of fibrosis according to the present invention. Figure 2 The blade portion includes a blade installed and inclined at an angle of about 5° and a column connected to the blade, wherein the blade has a length of about 23.5 mm and a width of about 6 mm. The length indicates the size in the horizontal direction, and the width indicates the size in the vertical direction.
[0089] E 11 T in the figure represents the torque applied to the blade when the blade descends at a rotation speed of 10 rpm, F represents the force applied to the blade when the blade descends at a rotation speed of 10 rpm, H is the measurement depth and represents the distance from H1 (a point approximately 2 mm from the top of the main body) to H2 (a point approximately 55 mm from the top of the main body).
[0090] E 8 T in the figure represents the torque applied to the blade when the blade is lowered at a rotation speed of about 100 rpm, F represents the force applied to the blade when the blade is lowered at a rotation speed of about 100 rpm, and H is the measurement depth and represents the distance from H1 (a point about 2 mm from the top of the main body) to H2 (a point about 55 mm from the top of the main body).
[0091] One cycle refers to the movement when the blade moves from H1 at the top of the blade to H2 at the bottom of the blade and then moves again to H1 at the top of the blade.
[0092] The degree of fibrosis can be measured by the following methods.
[0093] First, the powder for the electrode is placed in a split vessel of about 25 mm x about 25 mL. In this case, the amount of the powder for the electrode should fill up the vessel of about 25 mL.
[0094] Then, the blade portion is stirred under the following conditions. In this case, the blade portion moves downward to the bottom and then moves upward while rotating, and this movement is called one cycle. (Speed during the first to eighth cycles: about 100 rpm, speed during the ninth cycle: about 70 rpm, speed during the tenth cycle: about 40 rpm, speed during the eleventh cycle: about 10 rpm).
[0095] Finally, the degree of fibrosis is calculated according to Conditional Expression 1.
[0096] An electrode for a secondary battery according to the present invention may include the above-mentioned powder for an electrode.
[0097] The electrode may be an electrode for a lithium ion battery or an electrode for an all-solid-state lithium battery.
[0098] The ionic conductivity of the electrode may be in the range of about 0.20 mS to about 0.50 mS.
[0099] The specific capacity of the electrode may be in the range of about 190 mAh / g to about 193 mAh / g.
[0100] The composite density of the electrode may be in the range of about 3.40 g / cm3 to about 3.55 g / cm3.
[0101] The energy density of the electrode may be in the range of about 550 mAh to about 580 mAh.
[0102] Figure 3 A method for manufacturing a powder for an electrode and an electrode for a secondary battery according to the present invention is shown. Figure 3 , the method may include: manufacturing a mixture by dry mixing an active material, a solid electrolyte, a conductive material, and a particulate binder (S1); mixing the mixture to manufacture a mixture mass (S2); and pulverizing the mixture mass to manufacture a powder for an electrode (S3).
[0103] The mixture is prepared by dry mixing the active material, the solid electrolyte, the conductive material and the granular binder (S1)
[0104] Operation S1 is an operation of manufacturing a mixture by placing an active material, a solid electrolyte, a conductive material, and a particulate binder as materials necessary for manufacturing an electrode for a secondary battery and then mixing the active material, the solid electrolyte, the conductive material, and the particulate binder so that they are uniformly dispersed.
[0105] The active material, solid electrolyte, conductive material, and particulate binder are the same as those described above, and thus their description will be omitted.
[0106] The mixing is performed by a dry method without using a solvent, so that the effect of improving the processability can be obtained.
[0107] Mixing is not limited to typical physical mixing processes that may be used in the present invention, but may be performed using, for example, a high speed mixer / high shear mixer.
[0108] The rpm and time during mixing can vary depending on the manufacturing environment.
[0109] The mixture is mixed to produce a mixture mass (S2)
[0110] Operation S2 is an operation of mixing the mixture to fiberize the particulate binder and knead the particulate binder into a mixture mass.
[0111] The kneading process is a process that can satisfy the above characteristics, and generally, high shear mixing such as that performed in a jet mill is performed to fiberize the binder, but there is a problem that the active material is pulverized by mixing and the formed fibers may be cut. In the present application, this problem is solved by replacing the high shear mixing method with a low shear mixing method.
[0112] The kneading is not limited to a typical physical mixing process that can be used in the present invention, but may also be performed as a kneading process by a kneading device such as a kneader.
[0113] Through the kneading process, since the binder is fibrillated and the active material, the solid electrolyte, and the conductive material are combined or connected, a mixture mass having a solid content of 100% may be formed.
[0114] The kneading may be performed at a temperature ranging from about 50° C. to about 120° C. for 5 to 30 minutes.
[0115] When the kneading time is too short or the temperature is outside the above range and is low, there is a disadvantage of agglomeration because the fiberization and mixing of the binder cannot be well achieved, and when the kneading time is too long or the temperature is high, excessive fiberization of the binder may occur, and thus the performance of the electrode may deteriorate. When the binder is excessively fiberized, the composite density of the electrode may be reduced, and at the same time, the energy density may also be reduced. In addition, since the binder blocks the path of lithium ions, the ionic conductivity is also reduced.
[0116] The time and temperature during kneading may vary depending on the manufacturing environment.
[0117] Crushing mixture piece To produce powder for electrodes (S3)
[0118] Operation S3 is an operation of again pulverizing the mixture mass obtained in operation S2 to manufacture uniformly dispersed powder for an electrode, and may be a final preparation operation for manufacturing a sheet-shaped electrode.
[0119] Specifically, the mixture mass produced by operation S2 is kneaded, and the shape of the mixture mass becomes a large mass. When the mixture mass is directly pressed under strong pressure and high temperature to form a film, the density of the film may be too high or a uniform film may not be obtained. In order to obtain a uniform powder for an electrode, even for fiberization measurement, a pulverization process in operation S3 is required.
[0120] The pulverization is not limited to a conventional pulverization process that can be used in the present invention, but may be performed by a pulverizer (eg, a pin mill).
[0121] The pulverization can be performed using a screen with a particle size ranging from 400 μm to 600 μm. In this way, a uniformly dispersed powder can be obtained.
[0122] The degree of fiberization in conditional expression 1 is the measured degree of fiberization of the powder for the electrode as a result of the corresponding operation. When the kneading of operation S2 is performed, the degree of fiberization increases, and when the pulverization process of operation S3 is performed, the degree of fiberization decreases as the fibers are broken. However, when the deposition / lamination process of the electrode manufacturing operation is performed after operation S3, the degree of fiberization is restored because the fibers are reconnected.
[0123] The rpm and time during the pulverization process may vary depending on the manufacturing environment.
[0124] The method of manufacturing an electrode for a secondary battery according to the present invention may include: depositing the powder for an electrode manufactured as described above to manufacture a composite film (S4); and forming and laminating the composite film on at least one surface of a current collector to manufacture a dry electrode (S5).
[0125] Deposition of powder for electrode to produce composite film (S4)
[0126] Operation S4 is a preparation operation of manufacturing a dry electrode by depositing powder for an electrode and processing the powder into a film form.
[0127] The average thickness of the film may be in the range of about 50 μm to about 300 μm.
[0128] Deposition is not limited to the conventional deposition process available in the present invention, but can be deposited, for example, by a roll press. In this case, the temperature, pressure, gap between the rolls, and the roll press speed can be varied according to the manufacturing environment.
[0129] Since the composite film manufactured as described above does not include a solvent, the composite film has almost no fluidity, and is therefore easy to handle and processed into a desired shape, thereby being used to manufacture various types of electrodes. In addition, when the electrode composite material of the present invention is used for electrode manufacturing, since the drying process for removing the solvent can be omitted, the manufacturing processability of the electrode can be significantly improved, and problems such as fine powder of the active material or disconnection of the fiberized binder (fiberized binder) existing in the existing dry electrode manufacturing can be solved.
[0130] Forming and laminating a composite film on at least one surface of a current collector to produce a dry electrode (S5)
[0131] Operation S5 is an operation of manufacturing a dry electrode by forming and laminating a film on at least one surface of a collector.
[0132] Lamination may be an operation of rolling a film at a predetermined thickness and attaching it to a current collector.
[0133] Lamination is not limited to the conventional lamination process applicable to the present invention, but can be performed by, for example, a roller press. In this case, temperature, pressure, the gap between rollers and the rolling speed can be changed according to the manufacturing environment.
[0134] The composite film on the dry electrode manufactured as described above may have a porosity within an appropriate range.
[0135] The secondary battery according to the present invention may include the positive electrode manufactured as described above, a negative electrode, and an electrolyte interposed between the positive electrode and the negative electrode.
[0136] Hereinafter, the present invention will be described in detail with reference to the following Examples and Comparative Examples. However, the technical spirit of the present invention is not limited thereto.
[0137] Example 1 and Example 2 and Comparative Example 1 and Comparative Example 2
[0138] Example 1
[0139] S1. An active material (NCM811), a solid electrolyte (LPSCl), a conductive material (VGCF), and a binder (PTFE) are mixed without using a solvent to produce a mixture.
[0140] S2. Shear stress is applied to the mixture, and kneading is performed at a temperature of about 80° C. for about 5 minutes to fiberize the PTFE. In this case, the mixture is agglomerated to produce a clay-like mixture mass.
[0141] S3. The mixture mass is pulverized using a pin mill device to produce a powder for an electrode, which is a uniformly dispersed powder composite of about 500 μm or less.
[0142] Example 2
[0143] A powder for an electrode was prepared in the same manner as in Example 1, except that the kneading time in operation S2 of Example 2 was about 30 minutes.
[0144] Comparative Example 1
[0145] A powder for an electrode was prepared in the same manner as in Example 1, except that the kneading time in operation S2 of Comparative Example 1 was zero minutes (operation S2 was not performed).
[0146] Comparative Example 2
[0147] A powder for an electrode was prepared in the same manner as in Example 1, except that the kneading time in Operation S2 of Comparative Example 2 was 60 minutes.
[0148] Test Example 1: Comparison of the length and diameter of fibrous binders according to the degree of fibrillation
[0149] The test was performed to measure the degree of fiberization of the powder for electrode manufactured in Example 1 and Example 2 and Comparative Example 1 and Comparative Example 2, and to measure the scanning electron microscope (SEM), fiber length and diameter of PTFE as a binder. The results are shown in Tables 1 and Figures 4 to 7 shown.
[0150] [Method for measuring the degree of fibrosis]
[0151] 1. Put the powder for electrode into a dispensing container of about 25 mm x about 25 mL. In this case, the amount of powder for electrode should fill the container of about 25 mL.
[0152] 2. The blade section performs stirring under the following conditions.
[0153] In this case, the blade portion moves downward to the bottom and then moves upward while rotating, and this movement is called one cycle.
[0154] -Speed from the first to the eighth cycle: about 100rpm
[0155] - Speed of the ninth cycle: about 70rpm
[0156] -Speed of the tenth cycle: about 40rpm
[0157] - Eleventh cycle speed: about 10rpm
[0158] 3. Calculate the degree of fibrosis according to conditional expression 1.
[0159] [Conditional expression 1]
[0160] 2.7≤Fibrosis degree (E 11 / E 8 )≤3.6
[0161] [Formula 1]
[0162]
[0163] In conditional expression 1, E 11 E represents the eleventh period cycle value, and E cycle The value is the value calculated by Formula 1.
[0164] In conditional expression 1, E8 represents the E of the eighth cycle. cycle value, and E cycle The numerical value is the value calculated by Formula 1.
[0165] T, F, and H in Formula 1 are obtained by a measuring instrument including: a cylindrical body portion; and a blade portion installed on the body portion to rotate and configured to ascend and descend.
[0166] The blade portion includes a blade mounted and tilted at an angle of about 5°, and a post connected to the blade, wherein the blade has a length of about 23.5 mm and a width of about 6 mm.
[0167] E 11 T in the figure represents the torque applied to the blade when the blade descends at a rotation speed of 10 rpm, F represents the force applied to the blade when the blade descends at a rotation speed of 10 rpm, H is the measurement depth and represents the distance from H1 (a point approximately 2 mm from the top of the main body) to H2 (a point approximately 55 mm from the top of the main body).
[0168] E 8 T in the figure represents the torque applied to the blade when the blade is lowered at a rotation speed of about 100 rpm, F represents the force applied to the blade when the blade is lowered at a rotation speed of about 100 rpm, and H is the measurement depth and represents the distance from H1 (a point about 2 mm from the top of the main body) to H2 (a point about 55 mm from the top of the main body).
[0169] [Table 1]
[0170] item Example 1 Example 2 Comparative Example 1 Comparative Example 2 Kneading time (minutes) 5 30 0 60 Degree of fibrosis 2.7 3.6 2 4.5 Fiber length (mm) 4 5 1 5.6 Fiber diameter (μm) 3 4.5 2 8
[0171] Figure 4 A SEM image of the fibrous binder of Comparative Example 1 is shown. Figure 5 A SEM image of the fibrous binder of Example 1 is shown. Figure 6An SEM image of the fibrous binder of Example 2 is shown. Figure 7 A SEM image of the fibrous binder of Comparative Example 2 is shown.
[0172] According to the embodiments and comparative examples of the present invention. Figures 4 to 7 It can be seen that the longer the kneading time, the higher the degree of fiberization, and the larger the fiber length and diameter. In addition, in Comparative Example 1 in which kneading was not performed, only mixing was performed, and it can be seen that only slight fiberization was performed on the binder.
[0173] Test Example 2: Comparison of electrochemical performance and composite density according to the degree of fiberization
[0174] Electrodes for secondary batteries were manufactured using the powders for electrodes manufactured in the examples and comparative examples, and were tested to measure the electrochemical properties and composite density of the electrodes. The results are shown in Table 2 below.
[0175] [Method for producing electrode for secondary battery]
[0176] S4: The powder was put into a roller press (roller diameter: about 100 mm, roller temperature: about 80° C., about 5 rpm) to prepare a composite film.
[0177] S5: An electrode was manufactured by placing the composite film on one side of an aluminum foil (about 15 μm) and laminating the composite film by a laminating roller maintained at a temperature of about 100°C.
[0178] [Table 2]
[0179]
[0180] Referring to Table 2, it can be seen that the energy density is proportional to the specific capacity and inversely proportional to the composite density.
[0181] The higher the ionic conductivity, the better the specific capacity, but even if the ionic conductivity is high, the specific capacity as a result of the overall electrochemical and physical properties decreases when the powder used for the electrode is desorbed.
[0182] Furthermore, it was confirmed that as the degree of fibrillation increased, the path of lithium ions was obstructed, so the ion conductivity decreased, and the cohesiveness of the powder for an electrode increased, so that the binder effect increased and the composite density decreased.
[0183] That is, in order to design an electrode having a high energy density, it can be confirmed that a powder for an electrode having a degree of fiberization of about 2.7 or more and about 3.6 or less as defined in the present invention is suitable.
[0184] According to the present invention, by standardizing the fiberization degree, the fiberization degree of the dry electrode can be designed without using a solvent, so that an electrode with high energy density can be realized.
[0185] The effects of the present invention are not limited to the above-described effects. It should be understood that the effects of the present invention include all effects that can be inferred from the above description.
[0186] Although the embodiments of the present invention have been described, it will be appreciated by those skilled in the art that the present invention may be implemented in other specific forms without departing from the technical spirit or essential features of the present invention. Therefore, it should be understood that the above embodiments are not restrictive, but all embodiments are illustrative.
Claims
1. A powder for an electrode, include: Active substances; Solid electrolytes; Conductive materials; as well as Fibrous binder, Wherein, the fiberization degree of the powder satisfies the following conditional expression 1: [Conditional expression 1] 2.7≤Fibrosis degree (=E 11 / E 8 )≤3.6, [Formula 1] In the conditional expression 1, E 11 represents the E of the eleventh cycle calculated by the formula 1 cycle value, In the conditional expression 1, E 8 represents the E of the eighth cycle calculated by the formula 1 cycle value, and In the formula 1, T, F, and H represent the torque applied to the blade, the force applied to the blade, and the measurement depth, respectively.
2. The powder according to claim 1, in, The fibrous binder includes polytetrafluoroethylene (PTFE).
3. The powder according to claim 1, in, The active material includes NCM811, the solid electrolyte includes LPSCl, and the conductive material includes VGCF.
4. The powder according to claim 1, in, The length of the fibrous binder is in the range of 4 mm to 5 mm, or the diameter of the fibrous binder is in the range of 0.01 μm to 20 μm.
5. The powder according to claim 1, in, The fibrous binder may be included in an amount of 0.5 to 10 wt % based on 100 wt % of the powder for an electrode.
6. The powder according to claim 1, in, For each cycle from the first cycle to the eighth cycle, the blade stirs the powder in the container at a rotation speed of 100 rpm while descending and then ascending the measuring depth, and, wherein, while descending and then ascending the measuring depth, the blade stirs the powder in the container at 70 rpm in the ninth cycle, at 40 rpm in the tenth cycle, and at 10 rpm in the eleventh cycle.
7. An electrode for a secondary battery, comprising the powder according to claim 1.
8. The electrode according to claim 7, in, The electrode is an electrode for a lithium ion battery or an electrode for an all-solid-state lithium battery.
9. The electrode according to claim 7, in, The electrode for a secondary battery satisfies at least one of the following: ionic conductivity ranging from 0.20 mS to 0.50 mS, specific capacity ranging from 190 mAh / g to 193 mAh / g, composite density ranging from 3.40 g / cm3 to 3.55 g / cm3, and energy density ranging from 550 mAh to 580 mAh.
10. A secondary battery, include: A positive electrode manufactured using the powder according to claim 1; negative electrode; as well as An electrolyte is disposed between the positive electrode and the negative electrode.
11. A method for producing a powder for an electrode, the method comprising: include: manufacturing a mixture by dry mixing an active material, a solid electrolyte, a conductive material, and a particulate binder; mixing the mixture to produce a mixture mass; as well as pulverizing the mixture mass to produce the powder for electrode, Wherein, the fiberization degree of the powder for the electrode satisfies the following conditional expression 1: [Conditional expression 1] 2.7≤Fibrosis degree (=E 11 / E 8 )≤3.6, [Formula 1] Wherein, in the conditional expression 1, E 11 represents the E of the eleventh cycle calculated by the formula 1 cycle value, In the conditional expression 1, E 8 represents the E of the eighth cycle calculated by the formula 1 cycle value, Wherein in the formula 1, T, F and H represent the torque applied to the blade, the force applied to the blade and the measurement depth, respectively, wherein for each cycle from the first cycle to the eighth cycle, the blade stirs the powder in the container at 100 rpm while descending and then ascending the measuring depth, and From the ninth cycle to the eleventh cycle, while the measuring depth is lowered and then raised, the blade stirs the powder in the container at a rotation speed lower than 100 rpm, and the rotation speed in the eleventh cycle is 10 rpm.
12. The method according to claim 11, in, The binder includes polytetrafluoroethylene (PTFE).
13. The method according to claim 11, in, The active material includes NCM811, the solid electrolyte includes LPSCl, and the conductive material includes VGCF.
14. The method according to claim 11, in, The length of the binder is in the range of 4 mm to 5 mm, or the diameter of the binder is in the range of 0.01 μm to 20 μm.
15. The method according to claim 11, in, The mixing includes a kneading process using a kneader.
16. The method according to claim 17, in, The kneading process is performed at a temperature of 50° C. to 120° C. for 5 to 30 minutes. 17 . The method according to claim 11 , wherein the pulverizing is performed using a screen having a particle size of 400 μm to 600 μm.
18. The method according to claim 11, in, The binder may be included in an amount of 0.5 to 10 wt % based on 100 wt % of the powder for an electrode.
19. A method for manufacturing an electrode for a secondary battery, the method include: Depositing the powder for an electrode according to claim 1 to produce a composite film; and The composite film is formed and laminated on at least one surface of a current collector to manufacture a dry electrode.
20. The method according to claim 19, in, The electrode for a secondary battery satisfies at least one of the following: ionic conductivity ranging from 0.20 mS to 0.50 mS, specific capacity ranging from 190 mAh / g to 193 mAh / g, composite density ranging from 3.40 g / cm3 to 3.55 g / cm3, and energy density ranging from 550 mAh to 580 mAh.
Citation Information
Cited By
Online monitoring and end point judging method and system for dry-method electrode fibrosis process
CN121632936A
A method and system for online monitoring and endpoint determination of dry electrode fiberization process
CN121632936B
